Ethical challenges of healthcare professionals towards physician-assisted death requests in palliative care - Pacheco, Ana (2020)
Introduction: Discussions related to euthanasia and physician-assisted suicide by professionals working in palliative care often bring discomfort due to its sensitivity. Aim: Promote an ethical reflection on assisted death requests in a palliative care context. Materials and Methods: Based on a clinical case, ethical principles and the literature regarding euthanasia and medically-assisted suicide, a reflection on the theme and its complexity is intended. Results: To question basic ethical principles can lead to situations which are difficult to control. Some questions immediately stand out: is euthanasia a truly free and autonomous decision, if the individual is suffering? Is it honest to offer its legalization in a context where access to viable and quality alternatives to relieve suffering, such as palliative care, are not available for everyone? Isn’t suffering itself a hindrance to free choice? Conclusion: The ethical problem of legalizing euthanasia and physician-assisted suicide does not have right or wrong answers, and as it is based on values as absolute as dignity and respect for human life, it deserves a thoughtful reflection and discussion.